PENGARUH MODEL PEMBELAJARAN CORE BERBANTUAN MEDIA VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI 060954 MEDAN - Tarigan, Hanna Mentari; Rumiris Lumban Gaol; Patri Janson Silaban; Nova Florentina Ambarwati; Eka Kartika Silalahi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the CORE (Connecting, Organizing, Reflecting, Extending) learning model assisted by visual media on student learning outcomes in the IPAS subject for Grade IV at SD Negeri 060954 Medan Marelan. The research employed a One Group Pretest-Posttest Design with tests and questionnaires as data collection instruments. A total of 26 students participated as the research sample. The CORE model was implemented through structured steps that guided students to connect prior knowledge with new concepts, organize ideas, reflect on information, and deepen understanding through assignments. The results showed a significant improvement in the students’ average scores from 46.92 (pretest) to 85.34 (posttest), with 23 out of 26 students achieving mastery learning. The t-test analysis yielded tcount = 2.156 > ttable = 2.064, and the correlation coefficient was r = 0.403 > rtable = 0.388, indicating a moderate and significant relationship between the CORE model implementation and student learning outcomes. Furthermore, questionnaire responses revealed that students enjoyed the use of visual media, as it made learning more engaging, concrete, and easier to understand. These findings support cognitive learning theory and previous research showing that the CORE model enhances student engagement and conceptual understanding. It can be concluded that the CORE learning model assisted by visual media significantly improves student learning outcomes in IPAS, while fostering collaborative and meaningful learning experiences.